Ethical Dilemmas in Professional Planning Practice in the United States. Issue 4 (2nd October 2019) - Lauria, Mickey; Long, Mellone F.
Abstract: Problem, research strategy, and findings: We interviewed 61 practicing planners seeking deeper insights into what motivates their decisions and how they personally determine ethical behavior in the more contested and real-world situations they face. We asked how planners balance their own ethics, their individual take on professional planning ethics, their workplace cultures, and the specific principles embodied in professional codes. We combined these semistructured qualitative interviews with our prior survey results as part of a sequential mixed-methods research project to allow practitioners and academics to better understand the ethical bases of professional planning practice in the United States. Our interviewees confirmed most practicing planners regularly face ethical dilemmas in their professional practice. We find, in addition to the expected ethical dilemmas due to planners' commitments to both the scientific legitimacy of their technical analysis and the democratic legitimacy of political decision makers' implementation of those recommendations, most of our interviewees experienced ethical conflicts between their private ethics and those they use in their professional practice. Despite this ethical dissonance, their espoused behaviors were largely consistent with rule-based ethical frameworks, many of which are embedded in the AICP Code of Ethics and Professional Conduct. Though practicing planners felt the code was influential and useful, they also found it difficult to follow in practice. Finally, private-sector planners felt the code neglects to address the ethical concerns they face in practice. Takeaways for practice: Professional planners use different ethical frameworks depending on the context of the ethical dilemma faced and their workplace culture. Professional planners struggle with emotional and ethical dissonance in their attempts to balance their private ethics, their workplace norms and culture, and their professional code of ethics. The AICP Code could benefit from a round of revisions focusing on how the code can help minimize this inherent dissonance. Finally, professional planners should practice resolving ethical conflicts between their private and professional ethical perspectives as well as those between the legitimacy of technical planning expertise and democratic decision making.